Lactobacillus Supplementation Modulates Rumen Microbiota and Metabolism in Yaks Under Fattening Feeding Conditions: A Comprehensive Multi-Omics Analysis - Jianlei Jia; Pengjia Bao; Ning Li; Siyuan Kong; Min Chu; Qian Chen; Ping Yan (Animals)
The rumen is a critical organ that facilitates nutrient digestion in ruminant animals. However, the biological mechanisms by which rumen microbiota and its metabolites enable Lactobacillus to modulate rumen structure and maintain functional homeostasis under fattening feeding conditions remain poorly understood. In this study, 80 male Pamir yaks were selected, and a 170-day data collection phase was implemented. Correlation phenotypic data and multi-omics analyses (rumen microbial sequencing and rumen epithelial metabolomics) were conducted to investigate the regulatory effects of Lactobacillus supplementation on rumen microbiota and metabolic processes in a concentrate-based rearing yak model. The results demonstrated that feeding a high-energy diet may impair yak ruminal histomorphology, microbiota composition, and function while negatively modulating rumen microbiota–metabolic profiles associated with specific ruminal microbial communities and functions. Lactobacillus intervention treatment optimized the yak ruminal microbiome composition (mucous layer maturation was promoted, Prevotella and Ruminococcus abundance were reduced, and Fibrobacter and Muribaculaceae abundance were increased), thereby altering metabolite concentrations involved in various metabolic pathways under a high-energy feeding pattern (fatty acid metabolism pathways were upregulated). These alterations elucidated the beneficial impacts of the Lactobacillus supplementation strategy on yak ruminal health without compromising the high-energy intensive rearing pattern. Furthermore, the regulated ruminal microbiome metabolites may serve as potential biomarkers for future investigations into the functional impacts of Lactobacillus intervention treatment on healthy feeding strategies for yaks.